Association between wood cooking fuel and maternal hypertension at delivery in central East India. (August 2015) - Wylie, Blair J.; Singh, Mrigendra P.; Coull, Brent A.; Quinn, Ashlinn; Yeboah-Antwi, Kojo; Sabin, Lora; Hamer, Davidson H.; Singh, Neeru; MacLeod, William B.
<x xml:space="preserve">Abstract</x> Objective: Smoke from burning of biomass fuels has been linked with adverse pregnancy outcomes and hypertension among nonpregnant subjects; association with hypertension during pregnancy has not been well studied. We evaluated whether the use of wood cooking fuel increases the risk of maternal hypertension at delivery compared to gas which burns with less smoke. Methods: Information on fuel use and blood pressure was available for analysis from a cross-sectional survey of 1369 pregnant women recruited at delivery in India. Results: Compared to gas users, women using wood as fuel had on average lower mean arterial pressure (adjusted effect size − 2.0 mmHg; 95% CI: −3.77, −0.31) and diastolic blood pressure (adjusted effect size −1.96 mmHg; 95% CI: −3.60, −0.30) at delivery. Risk of hypertension (systolic >139 mmHg or diastolic >89 mmHg) was 14.6% for wood users compared to 19.6% for gas users although this did not reach significance after adjustment, using propensity score techniques, for factors that make wood and gas users distinct (adjusted prevalence ratio 0.76; 95% CI: 0.49, 1.17). Conclusions: Combustion products from the burning of biomass fuels are similar to those released with tobacco smoking, which has been linked with a reduced risk for preeclampsia. The direction of our findings suggests the possibility of a similar effect for biomass cook smoke. Whether clean cooking interventions being promoted by international advocacy organizations will impact hypertension in pregnancy warrants further analysis as hypertension remains a leading cause of maternal death worldwide and cooking with biomass fuels is widespread.